2017
DOI: 10.21082/jpasca.v12n2.2015.51-59
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Nanopartikel Zinc Oxide Dan Etilen Glikol Terhadap Sifat Fisik Dan Antimikroba Biodegradable Foam

Abstract: ABSTRAKKemasan biodegradable foam dibuat dari tapioka, ampok jagung, nanopartikel zinc oxide (ZnONP) dan pemlastis etilen glikol (EG). Kemasan diproses melalui cara thermopressing. Tujuan penelitian adalah untuk mengetahui pengaruh penambahan ZnONP dan EG. Penelitian ini dilakukan dengan menggunakan rancangan acak lengkap faktorial dengan 3 kali ulangan, dilanjutkan dengan uji Duncan pada α = 5%. Terdapat dua faktor yang digunakan yaitu ZnONP terdiri dari 3 taraf yaitu 0%, 1%, dan 2% serta EG yang terdiri atas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Research on the manufacture of edible films from starch with the addition of glycerol and zinc oxide is still a little done. Several previous studies that have used zinc oxide concentrations in the manufacture of edible films included sweet potato starch (Ervan, 2012), gadung tuber starch (Saputra et al, 2019), tapioca and corn ampok (Rahmatunisa, 2015), cassava starch (Ridwan, 2018), and soy protein (Putri et al, 2018). Several studies have revealed that there is an effect on changing characteristics from each addition of concentration or amount of ZnO nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the manufacture of edible films from starch with the addition of glycerol and zinc oxide is still a little done. Several previous studies that have used zinc oxide concentrations in the manufacture of edible films included sweet potato starch (Ervan, 2012), gadung tuber starch (Saputra et al, 2019), tapioca and corn ampok (Rahmatunisa, 2015), cassava starch (Ridwan, 2018), and soy protein (Putri et al, 2018). Several studies have revealed that there is an effect on changing characteristics from each addition of concentration or amount of ZnO nanoparticle.…”
Section: Introductionmentioning
confidence: 99%